Human Rights Defenders and Networks for their Protection: A response to repressive environments - Angel, Mauricio (Atâtôt - Interdisciplinary Journal of Human Rights (UEG), 2024)
International protection systems are based on the centrality of the State to guarantee the safety of human rights defenders (HRDs). In parallel, the dominant paradigm to protect HRDs at risk is the provision of individual protection measures. These solutions do not match the reality in many countries: States have regressed in their role as guarantor of human rights; and they have yielded their place to non-state actors, even entering into corrupt alliances with the latter, favoring the repression of communities that organize to defend their rights. The fieldwork experience of Protection International teams in countries of Latin America, Southeast Asia and sub-Saharan Africa has shown that the protection of HRDs is part of activism for claiming human rights as a social process and within its nature as social and relational beings. In other words, HRDs must be assumed as beings immersed in the struggles of their communities, their relationship with other social and political actors, and in their interaction with the territories, in the resistance to repressive and violent environments. It is from these relationships within networks that collective action in defense of human rights is favored - action that incorporates protection practices that help maintain resistance.